Frequência de empuxo na plataforma continental amazônica rasa - BRAGA, Anderson Movilha (2019)
The Amazon Continental Shelf (ACS) is subject to the interaction of physical forces from different sources, what produces highly energetic dynamic conditions in this environment. This dynamic processes make the ACS a unique environment with a high continental input coming from large estuarine systems that results in an extensive freshwater plume. However, the informations with focus in the mass field of this area is limited. This study aims verify the density field variations in this inner portion (30 m isobath), at approximately 100 km from Pará river mouth (0° 25,73' N/47° 41,88' W). Vertical profiles using a CTD (conductivity, temperature and depth) were performed over 12 months, between february 2018 and january 2019 (except may and june), totalizing 10 months of measurements. The conductivity data was converted using a new seawater state equation (TEOS-10), that determines the Temperatura (T) and Salinity (S) values. Brunt-Vaisala values frequency was used to analyze the density field. The results analysis indicated that TS stratification occurs only during the maximum discharge period, with gradients of 0.7ºC and higher than 25 salt units. In the minimum discharge conditions, there is no vertical stratification. The freshwater inputs has a strongly influence in the density field on this inner shelf wichs increasing the buoyancy forces, what differs of minimum discharge period that has no stratification and the buoyancy forces is reduced. Brunt-Vaisala frequency analysis indicated that temperature gradients were more relevant (in maximum discharge period) to the density field than the salinity gradients. From TS diagram it was possible to propose density values for the Amazon and Pará rivers plumes, admitting that these do not mix immediately, resulting in three layers with differents vertical density (Amazon and Pará rivers and ocean waters). Therefore, the instantaneous nature of the experiment indicated that density field variability is influenced only by Amazon and Pará rivers discharges, highlighting the temperature as important parameter in the variation of the density field in a system thats is commonly influenced by salinity gradient.